PENGARUH DOSIS PENAMBAHAN BOKASHI TERHADAP PROTEIN KASAR DAN SERAT KASAR PADA PEMOTONGAN PERTAMA RUMPUT GAJAH MINI (Pennisetum Purpureum cv. Mott) - Gilang Kurniawan; Farida Fathul; Muhtarudin Muhtarudin; Liman Liman (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2021)
This research aimed to determine the effect of bokashi dose on crude protein and crude fiber content at the first cut of dwarf elephant grass (Pennisetum Purpureum cv. Mott). This research was conducted in March—Juli 2020 in Sidodadi Asri village, Jati Agung district, South Lampung regency. This research used a completely randomized design (CRD) applying four treatments of bokashi dose, namely P0 (control), P1 (30 ton/Ha); P2 (40 ton/Ha); dan P3 (50 ton/Ha) with 3 replications each. The experimental unit of this study was plot of land with size of 200 cm x 200 cm. The obtained data were then analyzed using analysis of variance at 5% significant level and tested further with Orthogonal polynomial. The results showed that there was no significant effect (P>0.05) of different dose of bokashi on the crude protein and crude fiber content of dwarf elephant grass. Keywords: : Dwarf Elephant Grass, Dose, Bokashi,Crude Protein, Crude Fiber